Risk Perception and Economic Value Of Disaster Mitigation Case of Bantul Post Earthquake May 2006 - Suryanto, Suryanto; Kuncoro, Mudrajad (UI Scholars Hub, 2012)
This study aims to obtain empirical evidence of disaster mitigation in Bantul, Indonesia. The expected utility theory and impact of regional characteristics on individual perceptions was used to describe the disaster risk management process. The regional mapping based on hazard level was conducted by a Geographical Information System (GIS). Data used in this research were primary and secondary data. Primary data were obtained by distributing questionnaire to some respondents. Sample amounts used were 395 respondents. The research empirical contribution was to economic valuation method used towards safety and efforts to link regional characteristics, individual perception and also their willingness to conduct mitigation. The research practical contribution was to identify some key obstacles in disaster risk management. Based on multiple regression analysis, this study found that educational level, risk aversion degree, trust towards earthquake-resistant building, control ability, income level, classifi cation of hazard area contributes to higher Willingness To Pay (WTP) for mitigation. It also found that perception towards central governmental roles variable did not affect to WTP for mitigation. However, the income levels of the communities in Bantul positively correspond to WTP for mitigation suggesting that the fi ndings were consistent with the expected utility theory.